Earthquake and Tsunami Disaster Preparedness - Firzah, Andi (Journal Social Civilecial, 2023)
This article discusses Understanding Disaster, Classification of Disaster Mitigation of Tsunami Disaster.  Disaster is an event or series of events that threatens and disrupts people's lives and livelihoods which are caused, either by natural factors and / or non-natural factors or human factors, resulting in human casualties, environmental damage, property loss, and psychological impacts. This article aims to providing knowledge about disasters to the community, Reducing the risk or impact caused by disasters for communities in disaster-prone areas. Increase public knowledge in dealing with and reducing the impact or risk of disasters, so that people can live and do their activities safely. Knowing the methods, techniques and media of extension.